Estrategias metodológicas docentes en comprensión lectora y rendimiento académico en el área de Comunicación - Choquichanca Lavado, Rosa Eufemia (2020)
The basic foundation for all students’ educational future there is early education. That is why PIETBAF (Comprehensive  Family-Based Early Education Program), PAIGRUMA (Comprehensive Care Program for Mothers' Groups), SET (Early  Education Rooms) and CUNA MÁS were implemented.  All of these programs are important; however, very little  has actually been achieved because traditional teaching  methods persist. In this context, the aim of this research  was to establish whether or not a relationship exists between the methodological strategies employed by staff to  teach reading comprehension and the academic performance of five-year-old children in three educational institutions in the Lima district of San Juan de Miraflores. Using  Spearman’s rank correlation coefficient, we found that there is a significant positive relationship between the strategies employed to develop reading comprehension (such  as language games, reading aloud of children's stories in a  group, puppet theater, observation-description-creation,  poetry and expression-imagination-creativity) and academic performance.